Unusual evolution of tree frog populations in the Chernobyl exclusion zone. (26th January 2022) - Car, Clément; Gilles, André; Armant, Olivier; Burraco, Pablo; Beaugelin‐Seiller, Karine; Gashchak, Sergey; Camilleri, Virginie; Cavalié, Isabelle; Laloi, Patrick; Adam‐Guillermin, Christelle; Orizaola, Germán; Bonzom, Jean‐Marc
Abstract: Despite the ubiquity of pollutants in the environment, their long‐term ecological consequences are not always clear and still poorly studied. This is the case concerning the radioactive contamination of the environment following the major nuclear accident at the Chernobyl nuclear power plant. Notwithstanding the implications of evolutionary processes on the population status, few studies concern the evolution of organisms chronically exposed to ionizing radiation in the Chernobyl exclusion zone. Here, we examined genetic markers for 19 populations of Eastern tree frog ( Hyla orientalis ) sampled in the Chernobyl region about thirty years after the nuclear power plant accident to investigate microevolutionary processes ongoing in local populations. Genetic diversity estimated from nuclear and mitochondrial markers showed an absence of genetic erosion and higher mitochondrial diversity in tree frogs from the Chernobyl exclusion zone compared to other European populations. Moreover, the study of haplotype network permitted us to decipher the presence of an independent recent evolutionary history of Chernobyl exclusion zone's Eastern tree frogs caused by an elevated mutation rate compared to other European populations. By fitting to our data a model of haplotype network evolution, we suspected that Eastern tree frog populations in the Chernobyl exclusion zone have a high mitochondrial mutation rate and small effective population sizes. These data suggest that Eastern tree frog populations might offset the impact of deleterious mutations because of their large clutch size, but also question the long‐term impact of ionizing radiation on the status of other species living in the Chernobyl exclusion zone.